Wewenang Ombudsman Republik Indonesia Dalam Pemeriksaan Maladministrasi Tes Wawasan Kebangsaan Pegawai Komisi Pemberantasan Korupsi - Tuarita, Dedi Rusman; Sedubun, Victor Juzuf; Holle, Eric Stenly (Faculty of Law, Universitas Pattimura, 2022)
Introduction: Law Number 37 of 2008 concerning the Ombudsman gives authority to the Ombudsman to supervise and examine the implementation of public services for maladministration by state officials. However, in carrying out its authority, the ombudsman is faced with the problem of the KPK TWK and receives a report on the maladministration of the KPK employee TWK, so this raises the issue of whether the KPK employee TWK is part of maladministration and part of the administration of public services.Purposes of the Research: This study aims to find out the Ombudsman of the Republic of Indonesia has the authority to examine maladministration of the national insight test of employees of the corruption eradication commission. Methods of the Research: Type of research used is normative, namely research that is based on the rule of law that can provide an explanation of the problems being studied. The problem approach is the legal approach (statute approach) and the conceptual approach (conceptual approach). The collection of legal materials through primary legal materials is then linked to secondary legal materials.Results of the Research: Ombudsman of the Republic of Indonesia has the authority to examine maladministration of the national insight test of corruption eradication commission employees, as that the TWK of KPK employees is part of the object of maladministration examination which is a term related to the duties of the ombudsman according to the form and concept of maladministration and based on article 1 number 3 Law No. 37 of 2008. and TWK of KPK employees are part of public services within the scope of administrative services as referred to in Article 5 paragraphs (1) and (2), Article 46 paragraph (1) of Law Number 25 of 2009 and as well as maladministration in the implementation TWK which resulted in 51 KPK employees being dismissed, so that KPK employees reported TWK maladministration to the ombudsman. Thus the ombudsman carries out his duties and functions in examining the TWK of KPK employees according to the provisions of Article 6 and Article 7 of Law No. 37 of 2008 which gives the ombudsman the authority to receive maladministration reports.